Frankie saves Christmas - Lampard, Frank (Little, Brown Books for Young Readers London, 2014)
It's two nights before Christmas and Frankie, Charlie, Louise and Max are having a sleepover. But in the middle of the night they are magicked away to Lapland, where Santa tells them that a sack of Christmas presents has been stolen! The team set off to find them, but first have to face challenges from a naughty elf, a rogue reindeer and an abominable snowman ..